Novel Silica-Based Hybrid Adsorbents: Membrane Preparation and Copper(II) Adsorption Kinetics - Hu, Keyan; Liu, Junsheng; Wang, Kechun (Asian Journal of Chemistry, 2014)
A series of silica-based hybrid membranes were synthesized via sol-gel process. Thermogravimetric analysis was conducted to investigate their thermal stabilities. Adsorption experiment was performed to evaluate its adsorption performances for copper (II) removal. It is found that the temperature of thermal degradation could be arrived at near 230 ºC. The adsorption capacity of copper (II) on samples A-D increases with an increase in N-[3-(trimethoxysilyl)propyl]ethylene diamine content, suggesting that the functionalized groups will play main effect on copper(II) adsorption. Moreover, based on the dependency of adsorption capacity on contact time, copper (II) adsorption kinetics was calculated to evaluate its adsorption properties. It is confirmed that the adsorption of copper(II) on sample D followed the Lagergren second-order model. This finding demonstrates that these hybrid membranes can be used as adsorbents to separate and recover copper(II) from copper (II)-containing water.